Sense of Place, Fast and Slow: The Potential Contributions of Affordance Theory to Sense of Place - Raymond, Christopher M.; Kyttä, Marketta; Stedman, Richard (Frontiers in Psychology, 2017)
Over the past 40 years, the sense of place concept has been well-established across a range of applications and settings; however, most theoretical developments have ‘privileged the slow’. Evidence suggests that place attachments and place meanings are slow to evolve, sometimes not matching material or social reality (lag effects), and also tending to inhibit change. Here we present some key blind spots in sense of place scholarship and then suggest how a reconsideration of sense of place as ‘fast’ and ‘slow’ could fill them. By this, we mean how direct and immediate perception-action processes presented in affordance theory (resulting in immediately perceived place meanings) can complement slower forms of social construction presented in sense of place scholarship. Key blind spots are that sense of place scholarship: 1) rarely accounts for sensory or immediately perceived meanings; 2) pays little attention to how place meanings are the joint product of attributes of environmental features and the attributes of the individual; and; 3) assumes that the relationship between place attachment and behaviour is linear and not constituted in dynamic relations among mind, culture and environment.. We show how these blind spots can begin to be addressed by reviewing key insights from affordance theory, and through the presentation of applied examples. We discuss future empirical research directions in terms of: 1) how sense of place is both perceived and socially constructed; 2) whether perceived and socially constructed dimensions of place can relate to one another when perceived meanings become unsituated, and; 3) how place attachment may change over different stages of the life course based upon dynamic relationships between processes of perception-action and social construction. We conclude with insights into how processes of perception-action and social construction could be included in the design and management of urban landscapes.